Information and Communication Technologies in Lung Transplantation: Perception of Patients and Medical Teams - Sébastien Chanoine; Christelle Roch; Léa Liaigre; Matthieu Roustit; Céline Genty; Elisa Vitale; Jean-Luc Bosson; Christophe Pison; Benoît Allenet; Pierrick Bedouch (MDPI AG, 2022)
Optimal therapeutic management is a major determinant of patient prognosis and healthcare costs. Information and communication technologies (ICTs) represent an opportunity to enhance therapeutic management in complex chronic diseases, such as lung transplantation (LT). The objective of this study was to assess the preferences of LT patients and healthcare professionals regarding ICTs in LT therapeutic management. A cross-sectional opinion survey was conducted among lung transplant patients and healthcare professionals from the French lung transplantation centers. Five ICTs were defined (SMS, email, phone, internet, and smartphone application) in addition to face-to-face communication. An unsupervised approach by Principal Component Analysis (PCA) identified lung transplant patient profiles according to their preferences for ICTs. Fifty-three lung transplant patients and 15 healthcare professionals of the French LT centers were included. Both expected ICTs for treatment management and communication. Phone call, face-to-face, and emails were the most preferred communication tools for treatment changes and initiation. PCA identified four ICTs-related profiles ("no ICT", "email", "SMS", and "oral communication"). "Email" and "oral communication" profiles are mainly concerned with treatment changes and transmission of new prescriptions. The "SMS" profile expected reminders for healthcare appointments and optimizing therapeutic management. This study provides practical guidance to enhance LT therapeutic management by ICT intervention. The type of ICT used should take into account patient profiles to improve adherence and thereby the prognosis. A combination of strategies including information, education by a multidisciplinary team, and reminders is a promising approach to ensure an optimal management of our patients.